Benign neck swellings: a clinico-radio-pathological study - Irfana, Ayshath; Rai, Sheetal; Somayaji, K. S. Gangadhara (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: The present study aimed to know the common pathologies presenting as neck swellings in our region and their clinical, radiological, and cytopathological correlation in order to understand the nature of the lesion and accuracy of the diagnostic tools in finding a definitive diagnosis. Methods: Patients presenting with neck swelling to the ENT department of a tertiary care centre in Mangalore between June 2013 to July 2018 were included in the study based on retrospective and prospective sampling. Appropriate cytolopathological and radiological investigations were done and analyzed. Results: Out of 160 cases analyzed histopathology diagnosed 86.9% as benign and 13.1% as malignant. Radiologically 94.9% were diagnosed to be benign and 5.6% malignant whereas in cytological investigation 89.4% were diagnosed as benign and 6.9% as malignant while the remaining 3.8% cases were cytologically inconclusive. Intra operatively 6.9% cases had features of malignancy and rest 93% were benign. Thyroid was the most common benign neck swelling (73.2%) followed by cervical lymphadenopathy (6.9%) and thyroglossal cyst (5.6%). Conclusions: Discrepancy in clinico-radio-cytopathological correlation was highest in cases of thyroid swelling (more so in case of solitary thyroid nodule). None of the pre-operative investigations for neck swellings is 100% specific or definitive in diagnosing a benign from a malignant lesion in the neck.